Trends in the Utilization of Ankle Replacements: Data From Worldwide National Joint Registries - Perry, Thomas A.; Silman, Alan; Culliford, David; Gates, Lucy; Arden, Nigel; Bowen, Catherine (Foot & ankle international, 2021)
Background: Over the past decade, there has been a growth in the use of ankle replacements. Data from national joint registries have shown between-country differences in the utilization of ankle replacement. The reasons for these differences are, however, not well understood. Our aims were to describe and compare the annual incidence of primary ankle replacement between countries and, to examine potential reasons for variation over time. Methods: We used aggregate data and summary statistics on ankle replacements for the period 1993 to 2019 from national joint replacement registries in Australia, Finland, New Zealand, Norway, Sweden and the United Kingdom. From the annual recorded counts of procedures, demographic data were extracted on age, sex distribution, and indication(s) for primary ankle replacement. Registry-level summary results were also obtained on data completeness, counts of hospitals/units, and health care providers performing ankle replacements annually and data collection processes (mandatory vs voluntary). Annual ankle replacement incidence for all diagnoses and, by indication categories (osteoarthritis [OA] and rheumatoid arthritis [RA]), were calculated per 100 000 residential population aged ≥18 years. Results: For the period with data from all 6 countries (2010-2015), New Zealand had the largest annual incidence (mean ± SD) of 3.3 ± 0.2 ankle replacement procedures per 100 000 population whereas Finland had the lowest incidence (0.92 replacements). There were no common temporal trends in the utilization of ankle replacements. Over the years studied, OA was the predominant diagnosis in the United Kingdom, Australia, and New Zealand, whereas RA was the most common indication in Scandinavia. Conclusion: In these 6 countries, we found marked differences in the utilization of ankle replacements. Registry-related factors including data completeness and the number of hospitals/surgeons performing ankle replacements are likely to contribute to the observed between-country differences and need to be carefully considered when interpreting comparisons for this less common site for joint replacement surgery. Level of Evidence: Level III, retrospective study.